Competitive Activity of Weightlifters at the XXXII Olympic Games 2020 in Tokyo: Results and Prospects - V.G. Oleshko; Tаngxun Yang; O.P. Torokhtiy; S.O. Putsoff (H.S. Skovoroda Kharkiv National Pedagogical University, 2021)
Purpose: to study the indicators of the competitive activity of the strongest weightlifters in the world at the Games of the XXXII Olympiad 2020 and to identify trends for further increasing their sports results, taking into account weight categories and gender differences. Material and methods. By studying scientific literature, Internet resources, competition protocols, pedagogical observations, video recordings of competitions, we analyzed the achievements of 140 weightlifters who took part in the Games of the XXXII Olympiad 2020 in Tokyo and the number of countries they represented. All indicators of competitive activity and age characteristics were grouped according to the following principle: among the top 10 weightlifters in each weight category, as well as separately among the prize-winners of competitions among men and women. Results. The sports results of the top 10 weightlifters of each weight category among men and women who took part in competitions, age characteristics, the rate of achievements in a sports career, the level of approaches implementation and international competition were analyzed. Conclusions. Based on the analysis of the number of countries and licenses received by the athletes of these countries, world and Olympic records, the effectiveness of the performances of the world's leading weightlifters at the Olympic Games is shown. The optimal age for achieving the highest results, the age of the beginning of the sport for the prize-winners of the competition, the rate of achieving maximum results in a sports career, sports results, the level of implementation of competitive approaches, the rate of increase in achievements in competitive exercises, the value of starting results, the level of international competition in each weight category in men and women, the characteristics of the dynamics of the results of the most titled athletes during their sports career, who took part in the Olympic Games, are given.